Intensive Assistance for Writing A Scientific Paper (WASP) to Build Students with Achievement - Helmi Muhammad; Ahmad Taufiq; Suharyadi Suharyadi; Niki Puspita Sari; Abdillah Ubaidi; Hoirul Anam (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
ABSTRACT Writing scientific papers allows students to strengthen their cognitive abilities and creativity while also exploring their experiences, knowledge, and feelings. It takes a combination of education and empirical experience to realize it on a continuous basis. This activity achieves this goal by combining extensive real-world experience with a research-based scientific writing aid program. The target audience is MA Alif Laam Miim Surabaya students accompanied by a supervising teacher. This service activity uses the Asset Based Community Development technique. The activities included proposal drafting, presentation, research, report, and quarantine. This program resulted in eight research reports on various topics that were ready to be entered into scientific contests divided into social humanities, science and technology categories. Furthermore, the effects of this activity are recognized as having a favorable impact when compared to the previous intense mentorship program. This program's contribution is significant to develop students' critical and inventive academic personalities.